Interactions of umami with the four other basic tastes in equi-intense aqueous solutions. (June 2022) - Wang, Sijia; Dermiki, Maria; Methven, Lisa; Kennedy, Orla B.; Cheng, Qiaofen
Highlights: Umami taste does not enhance or suppress sweet, salty, sour or bitter in equi-intense solutions. Sweet, salty, sour and bitter significantly suppress umami taste in equi-intense solutions. Sodium chloride plus glutamate tastants maintained salty and savoury taste perception.